PERAN ORANG TUA DALAM PEMBENTUKAN MORAL SISWA DI MADRASAH TSANAWIYAH ASH-SHIDDIQI KELURAHAN KOWEL PAMEKASAN - Adawiyah, Robiatul; Supandi, Supandi (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2024)
Children are a trust for every family, so that they are educated to carry out religious teachings well and behave with good morals, respecting mother and father. Therefore, the morals taught by parents at home must be strong. This moral cultivation has a power that is difficult to eradicate. Therefore, moral teachings in the household play an important role. Therefore, both parents should know the rules of education so that in the future they can give birth to children who are good in their religion. The problem formulation in this research is the role and factors of parents in shaping students' morals to have good morals. The approach used in this research is qualitative. Data collection through interviews, observation, and documentation data analysis. The data that researchers have obtained in the field is then carried out in a reduction and display process and drawing conclusions. The results of this research are that the role of parents in moral formation is going well and the parents of the students are very supportive of the school. The inhibiting factor is that people put too much pressure when teaching their children so that the children are confused about what they are doing. The implications of this research are as follows: 1) Strengthening the Role of Parents in Education, 2) Collaboration between Madrasas and Parents, 3) Strengthening Character Education in Madrasas, 4) Religious Education at Home, 5) Socialization and Strengthening Positive Values.